2016
DOI: 10.1186/s13071-016-1675-2
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito communities and disease risk influenced by land use change and seasonality in the Australian tropics

Abstract: BackgroundAnthropogenic land use changes have contributed considerably to the rise of emerging and re-emerging mosquito-borne diseases. These diseases appear to be increasing as a result of the novel juxtapositions of habitats and species that can result in new interchanges of vectors, diseases and hosts. We studied whether the mosquito community structure varied between habitats and seasons and whether known disease vectors displayed habitat preferences in tropical Australia.MethodsUsing CDC model 512 traps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 55 publications
4
74
5
Order By: Relevance
“…3), there were no significant effects of logging treatment on either univariate diversity metric. These results differ from previous studies in Peru, Thailand, and Australia, which found strong declines in mosquito community diversity in more urbanised landscapes (Johnson et al, 2008;Thongsripong et al, 2013;Meyer Steiger et al, 2016). Because our study specifically isolated the effects of logging, it is possible that other characteristics of urbanisation explain the previously detected, much stronger, decreases in community diversity across a broad degradation or urbanisation gradient.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…3), there were no significant effects of logging treatment on either univariate diversity metric. These results differ from previous studies in Peru, Thailand, and Australia, which found strong declines in mosquito community diversity in more urbanised landscapes (Johnson et al, 2008;Thongsripong et al, 2013;Meyer Steiger et al, 2016). Because our study specifically isolated the effects of logging, it is possible that other characteristics of urbanisation explain the previously detected, much stronger, decreases in community diversity across a broad degradation or urbanisation gradient.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, lack of logging effects on mosquito diversity may be largely an artifact of the sampling methods we used. Previous studies that found effects of urbanisation on mosquito diversity (Johnson et al ., ; Thongsripong et al ., ; Meyer Steiger et al ., ) used traps that were selective for host‐seeking mosquitoes (e.g. light traps, BG sentinel), whereas this study used gravid traps, which were selective for ovipositing females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meyer Steiger et al . reported more mosquito species capable of transmitting pathogens to humans in grasslands than in pristine forest habitats, further showing that anthropogenic landscape changes could have implications for disease spill over. Alroy further suggested that this bimodal trend in mosquito species diversity and abundance at the opposite extremes of the disturbance gradient is probably due to the invasion of colonist species adapted to open habitats, transiently increasing the size of the species pool in disturbed forest scenarios.…”
Section: Discussionmentioning
confidence: 99%